87Sr/86Sr isotopic characterisation of dolina soils and flysch rocks from Trieste area (NE Italy) - Lenaz, Davide (Annales. Series historia naturalis, 1999)
87Sr/86Sr isotopic analyses have been carried on some dolina soils, sandstones and marl (flysch) from Trieste area (NE Italy) in order to look forthe parent material. By comparison of the obtained results, it is suggestedthat the main supplies to the genesis of these dolina soils are from the rocks constituting the flysch.
Keywords: izotopske analize; kamenine; prst; tržaški Kras